CONSTITUTIONAL COURT AND SPECIAL INDIGENOUS JURISDICTION: TRANSFORMATIONS AND ADVANCES IN COLOMBIA - Llano Franco, Jairo Vladimir (2024)
The recognition of the Special Indigenous Jurisdiction by the Constitutional Court has been decisive in the consolidation of the cultural and ethnic diversity of the Colombian context. For this reason, the article aims to analyze the transformations and advances that the Special Indigenous Jurisdiction has had with respect to some pronouncements of the Colombian Constitutional Court. The methodology used was mainly hermeneutics, which involved interpreting the constitutional case law and international treaties that address the issue of cultural recognition and indigenous autonomy regarding the power of indigenous peoples to resolve their conflicts using their own forms of justice and ancestral practices. This approach was carried out from the theoretical perspective of multiculturalism. This methodological approach allowed us to examine the impact and progress of the JEI, highlighting its contribution to the preservation and promotion of cultural diversity and identity, and legal pluralism. It also highlights its contribution to the safeguarding of the rights and autonomy of indigenous communities in Colombia, even to the point of linking it to recent events such as the indigenous mobilization.